Outdoor Study Method to Enhance Explanatory Text Writing in Indonesian Language Learning - Novia Zelayanti; Irwan Satria; Ixsir Eliya (Yayasan Darussalam Bengkulu, 2023)
This study aims to describe in detail the planning, enactment, and evaluation of an outdoor-study approach for the explanatory-text unit in Bahasa Indonesia instruction, and to identify the enabling and constraining factors that condition its success in a typical Indonesian public junior high school. Using a descriptive qualitative bounded case design focused on one intact class (Grade VIII-A, SMPN 13 Bengkulu), fieldwork spanned two Plan–Act–Observe–Reflect cycles (January–March 2022). Data sources comprised participant observation, lesson artefacts (observation sheets, drafts, rubrics), peer reviews, teacher feedback, and semi-structured interviews, and were analysed with Miles and Saldaña’s iterative procedures of data reduction, display, and conclusion drawing; trustworthiness was supported through triangulation, audit trails, member checks, and prolonged engagement. Based on research results, two key findings emerged. First, when structured by explicit objectives, focused observation instruments, annotated text modelling, and iterative feedback cycles, outdoor study substantially improved students’ rhetorical organisation, cohesion, use of technical vocabulary, and causal reasoning in explanatory writing. Second, effectiveness was enabled by careful task design, active teacher facilitation, and targeted language scaffolding, yet constrained by weather/time disruptions, uneven participation, documentation distractions, and limited vocabulary; these challenges were mitigated through time-boxing, role rotation, a no-face photo policy, and consistent rubric use, thereby stabilising writing quality across cycles. Overall, outdoor study functions not as a recreational supplement but as an evidence-based pedagogical strategy aligned with national curriculum demands, offering a replicable pathway for strengthening explanatory writing and causal reasoning while informing teacher practice and school-level design.